(untitled) (Research, Society and Development, 2019)
The Council of Pro-Rectors of Extension of the Brazilian Public Institutions of Higher Education, is an interdisciplinary, educational, cultural, scientific and political process that promotes the transformation between the University and other sectors of society. In this sense, the Federal Network of Professional, Scientific and Technological Education has been implementing several actions in order to develop and systematize activities as extensionists in the Federal Network, in the form of premises of the new institutional format that consolidates for a Brazilian professional education, with a new creation Federal Institutes of Education. Given the scope, this research aimed to characterize the descriptive profile of extension actions built on the campus of the Fortaleza do Ceará Federal Institute (IFCE), from January 2009 to May 2019. Data for a work of this type were collected from Extension Dean’s Management System (Sigproext), which is a tool used to record IFCE extension actions. This is a quantitative research, case study type and, for the purposes, descriptive. The indicators show that extension is a very present and constantly growing academic layer on campus, however, some suggestions for progress are pointed out, such as an analysis of special attention to the evaluation and results achieved with extension actions. Thus, it is hoped that this study, in addition to contributing to the extension monitoring on campus, will enable the promotion of future actions, and an orientation agenda that will be used for an extension evaluation in the institution.